Diffusion tensor imaging findings in children with sluggish cognitive tempo comorbid Attention Deficit Hyperactivity Disorder - Ünsel-Bolat, Gül; Baytunca, Muharrem Burak; Kardaş, Burcu; İpçi, Melis; İnci İzmir, Sevim Berrin; Özyurt, Onur; Çallı, Mehmet Cem; Ercan, Eyüp Sabri (Taylor and Francis Ltd.)
Objective: The construct of Sluggish Cognitive Tempo (SCT) is characterized by daydreaming, mental confusion, staring blankly and hypoactivity. Our main goal was to explore neuropsychological differences in Attention Deficit Hyperactivity Disorder-Inattentive presentation (ADHD-IA) groups with and without SCT symptoms compared to healthy controls. After detecting specific neuropsychological differences, we examined white matter microstructure using Diffusion Tensor Imaging (DTI) data obtained from 3.0 Tesla MRI scans of the cases with SCT symptoms comparing to Typically Developing (TD) controls. Method: In this study, we included 24 cases in the ADHD-IA group with SCT symptoms, 57 cases in the ADHD-IA group without SCT symptoms and, 24 children in the TD group. We applied tract-based spatial statistics to the DTI measures for obtaining fractional anisotropy (FA), axial, radial and mean diffusivity (AD, RD, MD) to explore white matter differences for the whole brain. Results: Omission error scores and longer reaction time scores were specifically associated with inattention symptoms. Commission error scores were significantly and specifically related to SCT symptoms. Cases with SCT symptoms presented increased FA in the bilateral anterior and posterior limb of the internal capsule, bilateral cerebral peduncle, and the fornix than TD group. Conclusions: Neurobiological differences in ADHD cases are still relatively unexplored. We suggest that including an assessment for SCT in the neuropsychological and neuroimaging studies of ADHD may provide more consistent results. © 2020 The Nordic Psychiatric Association.
Keywords: commission errors; DTI; Internal capsule; Neuroimaging; SCT